Strategi Peningkatan Profesionalitas Guru Kelas VI Daerah Binaan 3 Kecamatan Batang - Kunarso Kunarso; Iin Purnamasari; Bagus Ardi Saputro (Universitas PGRI Semarang, 2022)
This study examines the Strategy for Increasing the Professionalism of Class VI Teachers in the 3rd District of Batang District. The specific objectives of the study were to describe the professionalism of class VI teachers and to describe strategies for increasing the professionalism of class VI teachers in the target areas of 3 Batang District. The usefulness of research is that it can be used as relevant further study material. Discussion of